The Growth of Red Meranti (Shorea leprosula Miq) with Selective Cutting and Line Planting of Silvicultural System at the Forest Concessionaire PT. Sari Bumi Kusuma, Central Kalimantan - Prijanto Pamoengkas; Juniar Prayogi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Contribution of forest for development of this nation can not be regarded as small, so that the forests must be managed and used optimally and well preserved. As an effort to preserve and enhance timber production, PT. Sari Bumi Kusuma (PT. SBK) as one of the holders of Forest Concessionaire (IUPHHK-HA), have been applied Selective Cutting and Line Planting (TPTJ) silvicultural system in it’s management of natural forest production since 1999. Red Meranti (Shorea leprosula) is one of the flagship sppecies which are selected in TPTJ because it better growth than other Meranti sppecies.However, the growth of S. leprosula in line planting excessively unknown yet. This research aimed to know the diameter growth of S. leprosula 5 - 9 in TPTJ silvicultural system. Research conducted in Mei 2009 in PT. SBK’s areas. Data of diameter growth collected through observation of the 100 m x 100 m sampling plots (1 ha).Plot samples were taken in each age planting which are purposively selected based on the age of 5 to 9 years old of planting, where in each of the plot samples there are five lines of planting. Analysis of research data including diameter stand structure, data normality test, Mean Annual Increment (MAI), and curve of diameter growth. Diameter growth of of S. leprosula which planted in line generally sppreading normally, where the most frequency of individual tree is in the diameter class that represents the mean (average) of the stand diameter, and show sigmoid shape curve of the diameter growth. The average increment (MAI) of S. leprosula were highest at the age of seven year plantation i.e to 2.31 cm / year and the lowest at the age of five year plantation i.e 1.45 cm / year. The largest diameter found at the age of nine years after planting i.e 28.5 cm (average 19.7 cm).